Relationship between Job Satisfactions with Employee Commitment at PT. Barumun Agro Sentosa - Azhar Aziz (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to see the relationship between job satisfaction and employee commitment at PT. Barumun Agro Sentosa. The subjects in this study were employees aged 30-40 years with a length of work 4 to 10 years totaling 44 employees. The sampling technique used was purposive sampling technique. Data were collected using two scales, namely the scale of job satisfaction and the scale of employee commitment. Data analysis uses the product moment correlation technique (rxy) which is 0.424 with P = 0.000 <0.05, meaning that there is a positive and significant relationship between job satisfaction and employee commitment, which shows that the higher the employee's job satisfaction, the higher the employee's commitment. On the other hand, the lower the job satisfaction, the lower the employee commitment. Employee job satisfaction in this study is high because (empirical mean = 108.53.> hypothetical mean = 90 where the difference exceeds SD= 2.050). And employee commitment is also high, because (empirical mean = 102.28.> hypothetical mean = 92.5 where the difference exceeds SD = 3.110). The coefficient of determination from the correlation is R2 = 0.331. Job satisfaction contributes to employee commitment by 33.1%. The results of this study are in accordance with the hypothesis with the results of research in the field.